2008
DOI: 10.1002/eet.468
|View full text |Cite
|
Sign up to set email alerts
|

Creating the UK emission trading scheme: motives and symbolic politics

Abstract: This paper explores the business-led advocacy of the UK emission trading scheme with special focus on the symbolic benefi ts of emission trading for the business community. It traces the development of the UK Emissions Trading Group and links the group's preferences for emission trading to socio-economic, operational and legislative contexts. The analysis reveals that, although business originally supported emission trading as an alternative to taxation, more socio-symbolic motives shaped business interest in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 33 publications
(34 reference statements)
0
20
0
Order By: Relevance
“…Dominant amongst these are studies of the EU ETS (Cass 2005, Pinkse and Kolk 2007, Voß 2007, Skjaerseth and Wettestad 2008, and many other articles; Baldwin 2008, Braun 2009, van Asselt 2010, and the Clean Development Mechanism (CDM) (Green 2008, Boyd 2009, Pulver et al 2010, Shin 2010). There are, however, also some studies of the Regional Greenhouse Gas Initiative (RGGI) (Rabe 2004, Selin and VanDeveer 2011, New Zealand (Hood 2010, see also Bullock 2012, the UK pilot emissions trading scheme (Nye and Owens 2008) and the Voluntary Carbon Market (VCM, see Bumpus and Liverman 2008). Furthermore, some broad comparative articles explore the patterns of policy development across different markets (see in particular Betsill andHoffmann 2011 andPaterson 2012), while others explore the CDM in the context of a 'varieties of capitalism' argument 4 about how this shapes national CDM governance systems (Friberg 2009, Fuhr and Lederer 2009, Schroeder 2009).…”
Section: Situating the Special Issuementioning
confidence: 99%
“…Dominant amongst these are studies of the EU ETS (Cass 2005, Pinkse and Kolk 2007, Voß 2007, Skjaerseth and Wettestad 2008, and many other articles; Baldwin 2008, Braun 2009, van Asselt 2010, and the Clean Development Mechanism (CDM) (Green 2008, Boyd 2009, Pulver et al 2010, Shin 2010). There are, however, also some studies of the Regional Greenhouse Gas Initiative (RGGI) (Rabe 2004, Selin and VanDeveer 2011, New Zealand (Hood 2010, see also Bullock 2012, the UK pilot emissions trading scheme (Nye and Owens 2008) and the Voluntary Carbon Market (VCM, see Bumpus and Liverman 2008). Furthermore, some broad comparative articles explore the patterns of policy development across different markets (see in particular Betsill andHoffmann 2011 andPaterson 2012), while others explore the CDM in the context of a 'varieties of capitalism' argument 4 about how this shapes national CDM governance systems (Friberg 2009, Fuhr and Lederer 2009, Schroeder 2009).…”
Section: Situating the Special Issuementioning
confidence: 99%
“…Second, it analyses if membership of the UK ETS is associated with differences in the disclosure of organisations that participate in it. As such, this analysis contributes not only to the literature on corporate disclosure but it also helps to understand how disclosures may change over time under the influence of the UK ETS (see also Nye & Owens, 2008;Roeser & Jackson, 2005;Von Malmborg & Strachan, 2005). The findings of this research report on a very specific policy instrument in the UK context so generalisations are difficult to infer.…”
Section: Final Commentsmentioning
confidence: 88%
“…Indeed, von Malmborg and Strachan (2005) note that the main reason given by direct participants to engage in the UK ETS was to receive incentive payments. In the same vein, Nye and Owens (2008) suggested that organisations' primarily motivation in supporting economic instruments, such as emissions trading, is to achieve economic efficiency. However, the economic rationale for doing so is diminished or constrained by existing policy frameworks or wider socio-economic contexts.…”
Section: Insights From New Institutional Sociologymentioning
confidence: 99%
“…From 2013, the ETS cap is to be determined centrally, while procedures have been put in place to harmonise rules for the allocation of allowances. At the same time, greater use is being made of auctioning, leading to the abolition of NAPs (Nye and Owens, 2008;Van Asselt, 2010;Moore and Newey, 2013).…”
Section: Linkage Governancementioning
confidence: 99%